2014
DOI: 10.1038/cddis.2014.33
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal plasma induces head and neck cancer cell death: the potential involvement of mitogen-activated protein kinase-dependent mitochondrial reactive oxygen species

Abstract: Nonthermal plasma (NTP) is generated by ionization of neutral gas molecules, which results in a mixture of energy particles including electrons and ions. Recent progress in the understanding of NTP has led to its application in the treatment of various diseases, including cancer. However, the molecular mechanisms of NTP-induced cell death are unclear. The purpose of this study was to evaluate the molecular mechanism of NTP in the induction of apoptosis of head and neck cancer (HNC) cells. The effects of NTP on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
217
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(228 citation statements)
references
References 20 publications
9
217
2
Order By: Relevance
“…We obtained similar results investigating phosphatidylserine exposure using Annexin V which further supports the notion that induction of apoptosis was negligible (data not shown). This is in disagreement with findings of other groups which, however, used different plasma sources and/or cell lines in their experimentations [19][20][21]. These studies have shown plasma-reduced cancer cell viability and induced apoptosis in a dose-dependent manner.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…We obtained similar results investigating phosphatidylserine exposure using Annexin V which further supports the notion that induction of apoptosis was negligible (data not shown). This is in disagreement with findings of other groups which, however, used different plasma sources and/or cell lines in their experimentations [19][20][21]. These studies have shown plasma-reduced cancer cell viability and induced apoptosis in a dose-dependent manner.…”
Section: Resultscontrasting
confidence: 68%
“…apoptosis) in several tumor cells [17]. Applying plasmagenerated ROS, an induction of apoptosis was shown in melanocytic tumors in mice [18], in p53-mutated cancer cells [19], and in head and neck carcinoma in vivo [20] as well as in several other models [21]. Most studies have focused on tumor cell death after cold plasma treatment.…”
Section: Introductionmentioning
confidence: 98%
“…However, the overproduction of ROS may damage lipids, proteins, and DNA. 45 This study demonstrated that intracellular ROS production was increased significantly and peaked at 3 hours following PDT treatment ( Figure 4B). There are two explanations for this increase in ROS: 1) the photosensitizer may transfer its energy to form highly reactive 1 O 2 when oxygen is present in the environment as previous studies have reported that 1 O 2 may be one of the mediators of the imbalance in intracellular ROS; 29 and 2) the activated photosensitizer may react directly with organic substrates or via electron or hydrogen transfer to yield free radicals.…”
mentioning
confidence: 83%
“…Furthermore, NTP has been proposed as a novel anticancer therapeutic strategy [17]. This is based on the fact that NTP induces its cytotoxic effects through generating oxidative stress [18,19] specifically on cancer cells, including ovarian carcinoma [20,21], head and neck carcinoma [22], colorectal cancer and glioblastoma [23]. Interestingly, a recent study examining pancreatic carcinoma cells (MIAPaCa2) revealed the merit of the combined use of NTP and the anti-metabolite, gemcitabine [24].…”
Section: Introductionmentioning
confidence: 97%